Técnicas para construção de árvores filogenéticas - Viana, Gerardo Valdisio Rodrigues (2007)
Phylogenetic tree structures express similarities, ancestrality, and relationships between species or group of species, and are also known as evolutionary trees or phylogenies. Phylogenetic trees have leaves that represent species (taxons), and internal nodes that correspond to hypothetical ancestors of the species. In this thesis we rst present elements necessary to the comprehension of phylogenetic trees systematics, then ef cient algorithms to build them will be described. Molecular biology concepts, life evolution, and biological classi cation are important to the understanding of phylogenies. Phylogenetic information may provide important knowledge to biological research work, such as, organ transplantation from animals, and drug toxicologic tests performed in other species as a precise prediction to its application in human beings. To solve a phylogeny problem implies that a phylogenetic tree must be built from known data about a group of species, according to an optimization criterion. The approach to this problem involves two main steps: the rst refers to the discovery of perfect phylogenies, in the second step, information extracted from perfect phylogenies are used to infer more general ones. The techniques that are used in the second step take advantage of evolutionary hypothesis. The problem becomes NP-hard for a number of interesting hypothesis, what justify the use of inference methods based on heuristics, metaheuristics, and approximative algorithms. The description of an innovative technique based on local search with multiple start over a diversi ed neighborhood summarizes our contribution to solve the problem. Moreover, we used parallel programming in order to speed up the intensi cation stage of the search for the optimal solution. More precisely, we developed an ef cient algorithm to obtain approximate solutions for a phylogeny problem which infers an optimal phylogenetic tree from characteristics matrices of various species. The designed data structures and the binary data manipulation in some routines accelerate simulation and illustration of the experimentation tests. Well known instances have been used to compare the proposed algorithm results with those previously published. We hope that this work may arise researchers' interest to the topic and contribute to the Bioinformatics area.